Evaluating Learning Management Systems in University: Evidence in University in North Sulawesi - Maramis, Glenn D P (International Journal of Information Technology and Education, 2023)
Learning management systems (LMS) have been established at universities around the world including at Manado State University to connect students and faculty without the confines of a traditional classroom. It is a digital software environment designed to manage user engagement and provide learning content and resources to students. The aim of this study is to evaluate the use of learning management systems in universities. The method used in this study is the combined methods we used, namely library research and surveys. The library research method also uses secondary data collected from informative articles, books, and magazines. The results of this study found that the LMS used in universities is generally good, this is because the LMS system has been introduced and teachers must use it in daily lectures as well, it is very important to determine the feedback from students as LMS users. Previous studies have demonstrated varying understandings of the impact of implementing LMS in higher education in universities around the world. Therefore, this article provides some insights into the Impact of Utilizing E-learning Technology or LMS. This study concludes that the use of post-covid-19 LMS has shown a fairly good increase both for providers of learning content, namely teachers and system managers, and on the user side, namely students so that learning activities at universities have experienced quite an increase.